A deep convolutional neural network to simultaneously localize and recognize waste types in images. (1st May 2021) - Liang, Shuang; Gu, Yu
Highlights: A new dataset is construct for automatic recognition and classification of wastes. A multi-task learning model for recognizing and localizing wastes is proposed. A visual interpretation method is designed to show the model's distinctive ability. Remarkable performance and superiority over SOTA methods is obtained by the model. Abstract: Accurate waste classification is key to successful waste management. However, most current studies have focused exclusively on single-label waste classification from images, which goes against common sense. In this paper, we move beyond single-label waste classification and propose a benchmark for evaluating the multi-label waste classification and localization tasks to advance waste management via deep learning-based methods. We propose a multi-task learning architecture (MTLA) based on a convolutional neural network, which can be used to simultaneously identify and locate wastes in images. The MTLA comprises a backbone network with proposed attention modules, a novel multi-level feature pyramid network, and a group of joint learning multi-task subnets. To achieve joint optimization of waste identification and location, we designed the loss functions according to the concepts of focusing and joint . The proposed MTLA achieved performance similar to that of experts and had high scores for multiple tasks related to waste management. Its F1 score exceeded 95.50% (95.12% to 95.88%, with a 95% confidence interval) on the multi-label waste classification task, and the average precision score was over 81.50% (@IoU = 0.5) on the waste localization task. To improve interpretation, heatmaps were used to visualize the salient features extracted by the MTLA. The proposed MTLA is a promising auxiliary tool that can improve the automation of waste management systems.